Five true dog stories - Davidson, Margaret, 1936-; McCue, Lisa; Suba, Susanne, 1913- (New York : Scholastic, 1977)
A collection of five stories about real dogs that touched the lives of many people.
Dox, the greatest dog detective in the world -- Grip, the dog who was a thief -- Wolf, the dog who saved other dogs -- Barry, the dog who saved people -- Balto, the dog who saved Nome.
3.0
3-6
Keywords: Dogs -- Fiction; Dogs -- Fiction